Mitochondrial ROS in cancer: initiators, amplifiers or an Achilles’ heel? - Sabharwal, Simran S. (Nat Rev Cancer, 2014)
Mitochondria cooperate with their host cells by contributing to bioenergetics, metabolism, biosynthesis, and cell death or survival functions. Reactive oxygen species (ROS) generated by mitochondria participate in stress signalling in normal cells but also contribute to the initiation of nuclear or mitochondrial DNA mutations that promote neoplastic transformation. In cancer cells, mitochondrial ROS amplify the tumorigenic phenotype and accelerate the accumulation of additional mutations that lead to metastatic behaviour. As mitochondria carry out important functions in normal cells, disabling their function is not a feasible therapy for cancer. However, ROS signalling contributes to proliferation and survival in many cancers, so the targeted disruption of mitochondria-to-cell redox communication represents a promising avenue for future therapy.